Pertanggungjawaban Pidana Terhadap ODGJ Yang Melakukan Tindak Pidana Penganiayaan Yang Menyebabkan Kematian: ( Studi Kasus Di Polsek Sambi Boyolali ) - Pranawa, Burham; Saputri, Ananda Megha Wiedhar; Nurdiyanto, Ikhsan (Fakultas Hukum, Universitas Boyolali, 2023)
Abstract Cases of criminal acts of persecution causing death are serious violations and can violate human rights. The state has regulated these crimes in laws in order to achieve justice and balance between rights and obligations. Cases of the crime of abuse causing death are very rare cases, because in this case the perpetrator was a person with a mental disorder who beat the victim to the point of causing death. With this case, the authors are interested in the law used and what steps the police took to resolve the case. Based on the background of the problems above, the author intends to conduct research with the title